Accounting for the Decline in Private Sector Unionization: Representation Elections, Structural Change and Restructuring - Thomas Karier (Levy Economics Institute of Bard College, 1991)
During the 1980s several qualitative changes occurred in the union decline. First, net gains from certification (less decertification) elections fell to insignificant levels, tending to accelerate the union decline. On the other hand, union losses from the relative growth of nonunion services (structural change) also declined sharply as unionization rates became more homogeneous across sectors. As a consequence, virtually all changes in the unionization rate during the 1980s were caused by disproportional gains in nonunion employment within sectors (restructuring).
Keywords: 330